Implementation Of the Fulfillment of the Rights of Female Prisoners in Class II B Sukabumi Correctional Institution - Agung Leo Sasongko (Yayasan Adra Karima Hubbi, 2023)
Background. Human rights are rights that must be fulfilled and realized by everyone without exception, including prisoners in correctional institutions who are serving a sentence. Prisoners in correctional institutions are part of society in general, as humans they have rights that must be upheld by the law and government. Purpose. Female prisoners are different from men in terms of physical, psychological and psychological. Female prisoners also have natural rights that must be lived such as menstruation, pregnancy, childbirth and breastfeeding. So that female prisoners must receive special treatment. Method. This type of research is a type of field research (field research) using an empirical juridical approach, namely a research that deductively starts from analyzing the articles in the applicable laws and regulations linked to the facts in the field. The nature of this research is descriptive analytical about the fulfillment of the rights of female prisoners in the Class IIB Correctional Institution Sukabumi. Results. The results of this study indicate that the implementation of services to fulfill the rights of female prisoners has not been carried out properly due to various obstacles such as the quality and quantity of correctional officers who have not been fulfilled proportionally Conclusion. as well as facilities and infrastructure that are still not good and limited so that the fulfillment of the rights of prisoners cannot be done optimally.